2004
DOI: 10.1074/jbc.m310752200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Formaldehyde-induced Modifications in Proteins

Abstract: Formaldehyde is a well known cross-linking agent that can inactivate, stabilize, or immobilize proteins. The purpose of this study was to map the chemical modifications occurring on each natural amino acid residue caused by formaldehyde. Therefore, model peptides were treated with excess formaldehyde, and the reaction products were analyzed by liquid chromatographymass spectrometry. Formaldehyde was shown to react with the amino group of the N-terminal amino acid residue and the side-chains of arginine, cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
312
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(333 citation statements)
references
References 25 publications
15
312
0
6
Order By: Relevance
“…2). In this case the apparent loss of four hydrogens can be ascribed to the formation of two methylene bridges in an intramolecular cross-link that probably involves the Lys 4 and the N-terminal arginine [16] (Fig. 2).…”
Section: Preliminary Observationsmentioning
confidence: 97%
See 1 more Smart Citation
“…2). In this case the apparent loss of four hydrogens can be ascribed to the formation of two methylene bridges in an intramolecular cross-link that probably involves the Lys 4 and the N-terminal arginine [16] (Fig. 2).…”
Section: Preliminary Observationsmentioning
confidence: 97%
“…The stable isotope labeling techniques developed in the last two decades for relative quantitation experiments space from in vivo metabolic incorporation of heavy isotopes, or isotopically to fix tissues and cells and it is known as a cross-linking agent involving a wide set of amino acid residues [14,15]. Metz et al reported a systematic investigation on a series of synthetic peptides in the presence of glycine or NaCNBH 3 [16,17]. When the reducing agent is added to the mixture after 24 h incubation with formaldehyde, besides the expected dimethylated peptide a secondary product featuring 2 mass units less can be observed whereas a Schiff-base is generated at the N-termini.…”
Section: Introductionmentioning
confidence: 99%
“…Reticulantes, como o formaldeído, têm sido largamente utilizados para induzir modificações em proteínas e polissacarídeos. Exemplos incluem a reticulação da quitosana via formação de N-metileno-quitosana 17 ; reticulação da blenda alginato de sódio e hidroxietilcelulose com glutaraldeído em meio ácido seguido de um segundo processo de reticulação com uréia-formaldeído e ácido sulfúrico 18,19 ; reticulação por formaldeído e epicloridrina de açúcares obtidos da polpa de beterraba 20 ; formação de pontes estáveis de metileno em modelos de peptídeos 21 ; reticulação de colágeno 22 e proteína de semente de algodão 23,24 ; efeito sobre as propriedades mecânicas, permeabilidade ao vapor de água e solubilidade de glúten 25 , gliadina 26,27 , proteína de amendoim 28 , filmes de proteína isolada de soja 29,30 e, ainda, modificações em filmes de gelatina 31 . Neste estudo, os efeitos da adição de sorbitol como plastificante e do processo de reticulação com formaldeído, nas propriedades de filmes de alginato de sódio e alginato de sódio/sorbitol, foram investigados.…”
Section: Introducãounclassified
“…It is often released from wastewater of construction, textile, wood processing, furniture, and pharmacy industry (Tang et al 2009). Formaldehyde is a water-soluble compound, which can diffuse into many tissues rapidly, react with different macromolecules such as proteins and nucleic acids, cause DNA-DNA, protein-DNA, and protein-protein cross-links (Metz et al 2004;Merk and Speit 1998;Solomon and Varshavsky 1985). Therefore, it has a toxic effect on all organisms, the IARC (2006) (International Agency for Research on Cancer) has classified formaldehyde as a human carcinogen that causes nasopharyngeal cancer and probably leukemia.…”
Section: Introductionmentioning
confidence: 99%